A numerical study of the anti-icing heat load for a three-dimensional aircraft wing. (July 2020) - Ni, Zhangsong; Liu, Senyun; Zhang, Jun; Wang, Mao; Wang, Zixu
Abstract: In the design stage of an anti-icing system for an aircraft, the heat load on a protection surface must be correctly calculated. In this study, the heat load calculation method for an aircraft wing model was analyzed. The calculation process was presented and the correctness of the method was validated using existing published experimental data. And the effect of variation of incoming flow speeds, flight altitudes, and temperatures on the surface heat-load distribution was given. The results show that the heat load is mainly located at the leading edge of the wing. The maximum value of the heat load can reach 3500w/m2 and the closer to the tip of the wing, the larger the heat load value will be. The heat load curve has a trough in the middle and two shoulders at each side. The range of the non-zero region and the amplitude of the heat load is in proportion to the flow speed. However, the variation of altitude has a non-obvious effect on the heat load results. As the temperature rises, the amplitude of the heat load increases, but the distribution characteristic of the curve remains the same.